Physical description of selected tributary mouths and sheltered backwaters of the Athabasca and Clearwater rivers - Psutka, M. M.; Harvie, B. W. (1980)
A survey of the physical characteristics of the aquatic habitats at 25 locations on the Athabasca and Clearwater rivers was conducted during August 1978. The parameters determined at each site were current velocity and direction, depth, Secchi disc visibility, substrate composition, and temperature. The survey sites included sheltered areas downstream of points of land or islands, as well as tributary confluences. Downstream of points of land or islands, current velocity and flow direction were altered markedly and substrates were typically sands or silts. Physical changes evident at tributary confluences were Secchi visibility, current velocity, and flow direction. At the tributary mouths, sand and silt substrates were predominant in sheltered areas of low current velocity while coarser rock substrates occurred in other areas of the confluences.